Drought exacerbates negative consequences of high‐intensity cattle grazing in a semiarid grassland. Issue 3 (13th January 2020) - Souther, Sara; Loeser, Matthew; Crews, Timothy E.; Sisk, Thomas
Abstract: Grasslands managed for grazing are the largest land‐use category globally, with a significant proportion of these grasslands occurring in semiarid and arid regions. In such dryland systems, the effect of grazing on native plant diversity has been equivocal, some studies suggesting that grazing reduces native plant diversity, others that grazing increases or has little impact on diversity. One impediment toward generalizing grazing effects on diversity in this region is that high levels of interannual variation in precipitation may obfuscate vegetative response patterns. By analyzing a long‐term data set collected over a 20‐yr period in a semiarid grassland, we explicitly evaluated the role of climate in regulating the effect of cattle grazing on plant communities, finding that climate interacted with grazing intensity to shape grassland communities. Community composition of plots that were intensively grazed varied considerably in response to climatic variation and native species richness was low relative to ungrazed and moderately grazed plots. Following a severe drought in 2002, exotic species richness rapidly increased in the high‐intensity grazing plots. While this pattern was mirrored in the other treatments, exotic species richness increased to a greater extent and was slower to return to pre‐drought levels in the high‐intensity grazing plots. Overall, moderate grazing, even compared to grazing cessation, stabilized grassland communities through time, increased resilience to drought, and maintained the highest levels of native plant diversity and lowest levels of exotic diversity. These findings suggest that grazing, at moderate levels, may support grassland resilience to climate change in semiarid regions. However, grazing that exceeds tolerances, particularly in combination with extreme climatic events, like drought, can alter plant composition over relatively long timescales and possibly increase invasibility by nonnative species.